2007
DOI: 10.1182/blood-2007-03-080093
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of tolerance to the transgene product in a nonhuman primate model of AAV-mediated gene transfer to liver

Abstract: Adeno-associated virus (AAV)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
220
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(233 citation statements)
references
References 38 publications
(71 reference statements)
13
220
0
Order By: Relevance
“…As shown in Figure 4E, ICOS expression was significantly higher in CD4 ϩ CD25 low effector T cells than that in CD4 ϩ CD25 high Tregs in the spleen of both naive and plasmid-only treated mice. Therefore, in contrast to the general immune suppression achieved by a 2-drug combination (MMF and RPA), 26 anti-ICOS antibody aimed preferentially at ICOS high effector T cells induced by antigen activation after gene transfer/antigen presentation. This dynamic process is dependent on continuous exposure to antigen after gene transfer and leads to significant depletion of antigen-specific CD4 ϩ effector T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4E, ICOS expression was significantly higher in CD4 ϩ CD25 low effector T cells than that in CD4 ϩ CD25 high Tregs in the spleen of both naive and plasmid-only treated mice. Therefore, in contrast to the general immune suppression achieved by a 2-drug combination (MMF and RPA), 26 anti-ICOS antibody aimed preferentially at ICOS high effector T cells induced by antigen activation after gene transfer/antigen presentation. This dynamic process is dependent on continuous exposure to antigen after gene transfer and leads to significant depletion of antigen-specific CD4 ϩ effector T cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of combining 2 drugs, mycophenolate mofetil (MMF) and rapamycin (RPA), demonstrated that antibody responses against factor IX (FIX) was prevented after adeno-associated virus (AAV)-mediated gene transfer into the livers of nonhuman primates. 26 However, administration of either a single agent, or 2-agent combinations of MMF, cyclosporine A (CSA), and RPA were shown to have limited effects in a hemophilia A mouse model by only delaying immune responses after nonviral gene transfer. 27 Inhibitory antibodies appeared shortly after withdrawal of the drug(s).…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] Independent from these findings, evidence is accumulating that targeting AAV vectors specifically to the liver seems to induce tolerance to the transgene product. 13,47,48 Tolerance induction in liver: the role of regulatory T cells…”
Section: Immunity To the Encoded Transgenementioning
confidence: 99%
“…This was further confirmed by the use of an immunosuppressive regimen during AAV2 hepatic gene transfer in nonhuman primates, which resulted in the inhibition of regulatory T cells and the development of neutralizing antibodies to the transgene product. 48 These studies highlight the importance of regulatory T cells in maintaining tolerance to the transgene product. Furthermore, immune tolerance induction through AAV-mediated liver-directed gene transfer has enabled supplementary therapies such as enzyme replacement therapy 55 or muscle-directed gene transfer.…”
Section: Immunity To the Encoded Transgenementioning
confidence: 99%
See 1 more Smart Citation